Structural and Physicochemical Characterization of Extracted Proteins Fractions from Chickpea (Cicer Arietinum L.) as a Potential Food Ingredient to Replace Ovalbumin in Foams and Emulsions - Gutierrez-Cutino, M; Gutierrez-Cutino, M; Matiacevich, S; Soto-Madrid, D (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Chickpeas are the third most abundant legume crop worldwide, having a high protein content (14.9–24.6%) with interesting technological properties, thus representing a sustainable alternative to animal proteins. In this study, the surface and structural properties of total (TE) and sequential (ALB, GLO, and GLU) protein fractions isolated from defatted chickpea flour were evaluated and compared with an animal protein, ovalbumin (OVO). Differences in their physicochemical properties were evidenced when comparing TE with ALB, GLO, and GLU fractions. In addition, using a simple and low-cost extraction method it was obtained a high protein yield (82 ± 4%) with a significant content of essential and hydrophobic amino acids. Chickpea proteins presented improved interfacial and surface behavior compared to OVO, where GLO showed the most significant effects, correlated with its secondary structure and associated with its flexibility and higher surface hydrophobicity. Therefore, chickpea proteins have improved surface properties compared to OVO, evidencing their potential use as foam and/or emulsion stabilizers in food formulations for the replacement of animal proteins. © 2022 by the authors.